Discovery of 2-[2-(5-nitrofuran-2-yl)vinyl]quinoline derivatives as a novel type of antimetastatic agents. Issue 1 (1st January 2015) - Tseng, Chih-Hua; Tzeng, Cherng-Chyi; Chiu, Chien-Chih; Hsu, Chih-Yao; Chou, Chon-Kit; Chen, Yeh-Long
Graphical abstract: Abstract: A number of 2-furanylvinylquinoline derivatives were synthesized and evaluated for antiproliferative activities against the growth of four cancer cell lines including non-small cell lung cancer (A549 and H1299), breast cancer (MCF-7 and MDA-MB-231) and normal diploid embryonic lung cell line (MRC-5). Among them, ( E )-6-methoxy-3-(4-methoxyphenyl)-2-[2-(5-nitrofuran-2-yl)vinyl]quinoline (10c ) was found low cytotoxic in all cancer cells and normal cell. The aim of this study was to investigate the anti-invasive and anti-metastatic activity of compound 10c in H1299 human lung cancer cells. In this study, compound 10c inhibited the migration and invasion of cells in a concentration-dependent manner by wound healing assay and transwell invasion assay. Furthermore, the inhibition of both phosphorylation of Akt and ERK by compound 10c may be critical for cell migration and this may result in the down-regulation of several factors associated with cellular migration, including β-catenin transcription factor, Bcl-2 and COX-2. Interestingly, the treatment of compound 10c did not affect the expression level but reduced the activities of the MMP-2 and -9. The phosphorylation level of stress-activated kinase p38 was significantly increased following compound 10c treatment. To sum up, compound 10c had potential to suppress the migration and invasion of H1299 cancer cells in vitro and it could serve as a promising drug for the treatment of cancer metastasis.